Some Special Problems in Peritoneal Dialysis - Ekart, Robert (IntechOpen, 2016)
This book covers some special issues relevant to peritoneal dialysis and is a guide to the clinical practice of peritoneal dialysis. A team of international experts presents the latest information about novel peritoneal solutions, pharmacological preservation of peritoneal membrane, peritoneal dialysis catheters, assessment of volume status in PD patients, management of exit-site infection, microbiology of PD peritonitis, peritoneal dialysis in acute renal failure, and peritoneal dialysis and pregnancy.